2009
DOI: 10.1002/bdra.20582
|View full text |Cite
|
Sign up to set email alerts
|

Anencephaly and spina bifida among Hispanics: Maternal, sociodemographic, and acculturation factors in the National Birth Defects Prevention Study

Abstract: Less acculturated Hispanic parents seemed to be at highest risk of NTDs. For anencephaly, U.S.-born and English-speaking Hispanic parents were also at increased risk. Finally, from an etiologic standpoint, spina bifida and anencephaly appeared to be etiologically heterogeneous from these analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
59
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 34 publications
2
59
1
2
Order By: Relevance
“…For this reason, during the antenatal period, folic acid supplementation is important for the prevention of NTDs. For supplementation, folic acid has been added to grain products in developed countries for the last 20 years [16]. We found that none of the mothers had folic acid support before and during pregnancy, which may indicate the necessity of adding folic acid to grain products in our country.…”
Section: Discussionmentioning
confidence: 92%
“…For this reason, during the antenatal period, folic acid supplementation is important for the prevention of NTDs. For supplementation, folic acid has been added to grain products in developed countries for the last 20 years [16]. We found that none of the mothers had folic acid support before and during pregnancy, which may indicate the necessity of adding folic acid to grain products in our country.…”
Section: Discussionmentioning
confidence: 92%
“…The protective effect associated with being foreign born is not consistent for all birth outcomes. For example, foreign-born women and less acculturated women tend to be at greater risk of gestational diabetes and of delivering infants with serious neural tube defects than U.S.-born women (McDonald et al, 2008;Canfield et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Using data from twenty-five population-based surveillance systems from 2005-2007, Hispanic women were estimated to be 1?21 (95 % CI 1?11, 1?31) times more at risk for an NTDaffected pregnancy than non-Hispanic white women (6) . Other researchers have also suggested that acculturation could be a risk factor for NTD (13,24,25) . However, this relationship has not been reported consistently and has been shown to vary for other birth defects (24) .…”
Section: Discussionmentioning
confidence: 99%